Transformative hope towards subversive resilience:: The ethical roles of newspaper articles by Indian writers during the Covid-19 outbreak - Diego Sánchez, Jorge (International Journal of English Studies, 2025)
This article studies Indian writing in the English language published in English newspapers (Indian, Bangladeshi, British, US) during the first wave of the Covid-19 outbreak in India (March 22–May 25, 2020). The selected authors include Arundhati Roy, Tishani Doshi, Anuradha Roy, and Prayaag Akbar, to illustrate the transnational consequences of the Covid-19 outbreak in different areas of India and analyse the narratology of resilience to articulate ethical knowledge against regional, national, and international stereotypes. I propose the concept transformative hope as an oppositional complaint (Bargués et al., 2024; Braithwaite, 2004; Giroux, 2004) against political and representational systems of domain articulated against the capitalist politics of who can afford to survive. This study shows a possible subversive resilience (Bracke, 2016; Darías-Beautell, 2020; Fraile-Marcos, 2020a; O’Brien, 2015) that, together with writing and reading, can implement alliance, rather than affiliation, and praises an ethical and transformative hope that dissents against the resilient appropriation of neoliberalism to benefit from tragedies like Covid-19.